Liquid fibres and their networks from cellulose-based liquid crystalline solutions. Issue 13 (8th December 2018) - Canejo, J. P.; Fernandes, S. N.; Godinho, M. H.; Pieranski, P.
ABSTRACT: The production of fibres and films with enhanced mechanical properties, from liquid crystalline cellulose-based systems, has always been a challenge. Previous works indicate that the use of spinning and electrospinning allows the fabrication of non-woven membranes with optical and mechanical characteristics distinct from casting films. The subsequent interactions of the micro/nanofibres inside membranes can modify their topology and geometry so they are found crucial for tuning the membranes' properties. In this work, we deal with the evolution of networks made of highly stretched liquid filaments. Three main mechanisms were identified: the thinning of filaments feeding growing nodes, breaking of the thinner filaments before the thicker ones and the zipping of pairs of filaments crossing at small angles. Graphical Abstract: